2016
DOI: 10.1088/2050-6120/4/4/045004
|View full text |Cite|
|
Sign up to set email alerts
|

Experimental and theoretical study of hydroxyquinolines: hydroxyl group position dependent dipole moment and charge-separation in the photoexcited state leading to fluorescence

Abstract: Optical absorption and fluorescence (FL) spectra of 2-, 6-, 7-, 8-hydroxyquinolines (2-,6-,7- and 8-HQs) have been measured at room temperature in the wide range of solvents of different polarities, dielectric constant and refractive index. The ground state dipole moment (µ ) and excited state dipole moment (µ) of 2-, 6-, 7- and 8-HQs were obtained using solvatochromic shift (SS) methods and microscopic solvent polarity parameters (MSPP). Change in the dipole moment (Δµ) between the ground and photo-excited st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Faber et al [ 16 ] reported a mean absolute error of 0.10 D between B3LYP calculations and experiment using 49 molecules. Others have also reported good agreement between experimental and DFT calculated DMs for more complex molecules [ 17 , 18 ]. Experimental measurements and quantum chemistry calculations were performed in the gas phase.…”
Section: Introductionmentioning
confidence: 55%
“…Faber et al [ 16 ] reported a mean absolute error of 0.10 D between B3LYP calculations and experiment using 49 molecules. Others have also reported good agreement between experimental and DFT calculated DMs for more complex molecules [ 17 , 18 ]. Experimental measurements and quantum chemistry calculations were performed in the gas phase.…”
Section: Introductionmentioning
confidence: 55%
“…Filip et al investigated the electronic structure of the 8-hydroxyquinoline molecule in some solvents and thus an ESIPT structure has been explained for this molecule [19]. Electronic structure and dipole moments estimated by using polar and aprotic solvents the 2-,6-,7-, 8-hydroxyquinolines were researched by Mehata et al [20]. The observed electronic transition wavelength values for both absorption and emission spectra in these works were smaller than those in the present work, because the phenoxy substituent gives rise to longer wavelengths.…”
Section: Electronic Transitionsmentioning
confidence: 99%
“…In addition, these calculations were used to find dielectric and refraction index functions and Onsager cavity radius. Moreover, the statistical parameters found in the experimental dipole moment calculations are listed in [20]. The ground state dipole moment of HSQ with hydroxystyryl substituent decreases, while its excited state dipole moment increases.…”
Section: Electric Dipole Momentsmentioning
confidence: 99%
See 1 more Smart Citation